25-7v=10(v-6)

Simple and best practice solution for 25-7v=10(v-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25-7v=10(v-6) equation:


Simplifying
25 + -7v = 10(v + -6)

Reorder the terms:
25 + -7v = 10(-6 + v)
25 + -7v = (-6 * 10 + v * 10)
25 + -7v = (-60 + 10v)

Solving
25 + -7v = -60 + 10v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-10v' to each side of the equation.
25 + -7v + -10v = -60 + 10v + -10v

Combine like terms: -7v + -10v = -17v
25 + -17v = -60 + 10v + -10v

Combine like terms: 10v + -10v = 0
25 + -17v = -60 + 0
25 + -17v = -60

Add '-25' to each side of the equation.
25 + -25 + -17v = -60 + -25

Combine like terms: 25 + -25 = 0
0 + -17v = -60 + -25
-17v = -60 + -25

Combine like terms: -60 + -25 = -85
-17v = -85

Divide each side by '-17'.
v = 5

Simplifying
v = 5

See similar equations:

| F(x)=105x | | 10y+5x=30 | | 2c+10=c-2 | | -12x=-228 | | 12x+32=10+y | | 2y^2-6x+1=0 | | 3m^3+192= | | -70=14n | | 12(600)=x | | 2(-3x+5)-6x=-3(x+4) | | 14-5x+9x=-2(-7x+3) | | 8n-17=0 | | x^2-2xy+8=0 | | x-9=3x+15 | | -9x+1=2x-8 | | 3(y-6)=8y+22 | | P-3=11 | | 7+4=27 | | 6x+9=-4 | | N-3=-21 | | 2cosx=2-3sinx | | N-3=-23 | | -5w+3(w+5)=27 | | N^2+3n-128=0 | | K+12=1 | | 30-10x=-7(6-x) | | 7h+9=32 | | 19=a+1 | | 6p-6+40p=2+34p | | 6x+5-8x=-(2x-5) | | 1 = m3– 1 | | 7y-5-5y+2=0 |

Equations solver categories